DAMPAK MEKANISASI PERTANIAN TERHADAP PEREKONOMIAN ANGGOTA KELOMPOK TANI SUMBER REJEKI KECAMATAN BANGSALSARI, KABUPATEN JEMBER - Prayuginingsih, Henik; Fauzi, Nurul Fathiyah; Badriyah, Rahel; Jannah, Fahirotul (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
Aims of study were : (1) analyze factors that affected farmers' decision to apply mechanization or not, (2) analyze the impact of mechanization on the economy of the member of paddy farmer group Sumber Rejeki. The study was done purposively at a group of farmer Sumber Rejeki, Sukorejo Village, Sub Bangsalsari Sub District, District of Jember with 20 mechanization user farmers, and 20 non-user farmers as samples in rainy planting season Oktober - December 2019. Data were analyzed by logit model regression, income and productivity analysis, and FFA. The results were: (1) factor which was affected farmers to decide applied agriculture mechanization was the availability of agriculture labor and this effect was significant, while wide of land, farmer’s age, and participation in elicitation/training about agriculture mechanization were affected not significantly. (2) the economic impact of mechanization on the member of Sumber Rejeki was raising productivity and farmers income, which productivity of farmers who used mechanization was 4,05 ton/ha and income was Rp 9.018,952/ha, while non-user farmers just got productivity 3,51ton/ha and income was Rp 6.819,529/ha.